CSR Communication Strategy of PT Angkasa Pura Indonesia Adi Soemarmo Airport Branch in Building Corporate Image - Puji Lestari; Riski Apriliani (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study is motivated by the importance of Corporate Social Responsibility (CSR) as a corporate communication strategy in building a positive image, particularly in the aviation sector closely connected to surrounding communities. The research aims to analyze the CSR communication strategy of PT Angkasa Pura Indonesia, Adi Soemarmo Airport Branch, through its greening program in Pandeyan Village, Ngemplak District, Boyolali Regency. The program focuses on the environmental aspect (Planet) within the Triple Bottom Line concept by distributing tree seedlings and compost fertilizer. Using qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and documentation from company archives and media publications. The findings show that the CSR strategy is participatory, reflected in the village government’s initiative, community involvement, and the company’s presence during program implementation. Consistency between communication messages and actions strengthens the company’s positive image. The use of mass and social media, including the official Instagram account @adisoemarmoairport, expands the reach of publications as a form of transparency. The implementation of sustainability is reflected in the program’s continuity in several villages, although accountability has not been fully achieved. These findings affirm that CSR functions as an effective communication strategy in building relationships with stakeholders.